Using atmospheric emissions as CO2 source in the cultivation of microalgae: Productivity and economic viability - Assis, Tamires Condé de; Calijuri, Maria Lúcia; Assemany, Paula Peixoto; Pereira, Alexia Saleme Aona de Paula; Martins, Márcio Arêdes (Journal of Cleaner Production, 2019)
This study approached the use of atmospheric emissions as a source of carbon for the cultivation of microalgae in high rate ponds (HRPs), continuously fed with domestic sewage pre-treated in a septic tank. To do so, two HRPs were used: one had CO2 at a concentration of 99.9% (HRP 1), and the other had gas from the combustion of gasoline (HRP 2). Biomass yield, sewage treatment efficiency and the economic viability of using these two sources were assessed. The results showed that the CO2 source did not influence the domestic sewage treatment or the yield and biochemical composition of biomass, since there was no statistical difference (p < 0.05) between the values measured for both ponds. The mean yield values were 6.00 and 6.12 g m−2 day−1, respectively for the HRPs 1 and 2. As for the mean concentrations of ammonia nitrogen and the percentages of removal of chemical oxygen demand (COD), they were in the average for both HRPs (26.4 mg L−1 and 31.2%). The negative Net Present Values (NPV) showed that in this study the investments for installing external CO2 sources are not economically viable for any of the two studied sources, when the biomass produced in the HRPs is used for the production of biofuels and as source of protein for animal feeding. The initial investments, allied to the prices of the biomass, were the factors that mostly influenced the economic analysis, contributing to the lack of attractiveness in this scale. Despite this, the use of atmospheric emissions along with domestic sewage as a cultivation medium means the biomass produced in this study has less environmental impact when compared to similar biomasses.
Keywords: Investment analysis; High rate ponds; CO2 supply; Effluent treatment